2013
DOI: 10.1109/tip.2013.2267393
|View full text |Cite
|
Sign up to set email alerts
|

No-Reference Quality Assessment of Natural Stereopairs

Abstract: We develop a no-reference binocular image quality assessment model that operates on static stereoscopic images. The model deploys 2D and 3D features extracted from stereopairs to assess the perceptual quality they present when viewed stereoscopically. Both symmetric- and asymmetric-distorted stereopairs are handled by accounting for binocular rivalry using a classic linear rivalry model. The NSS features are used to train a support vector machine model to predict the quality of a tested stereopair. The model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(140 citation statements)
references
References 36 publications
3
137
0
Order By: Relevance
“…It can be concluded that Q3D-RBM performs comparably with FF QA metrics, while it is a RR 3D QA metric, independent of distortions type. The second experiment was done on the Phase II of the LIVE 3D Image Quality Database [12,24]. This contains 8 reference images with 45 distorted images for each reference one.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…It can be concluded that Q3D-RBM performs comparably with FF QA metrics, while it is a RR 3D QA metric, independent of distortions type. The second experiment was done on the Phase II of the LIVE 3D Image Quality Database [12,24]. This contains 8 reference images with 45 distorted images for each reference one.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Pixels associated with disparity errors are often dissimilar with features computed on the corresponding disparity shifted pixels in the other view. The authors of [39] defined a disparity uncertainty map to estimate the uncertainty produced by DSSIM and used it as a feature to improve the task of 3D no-reference distortion assessment. The uncertainty is defined as:…”
Section: Uncertainty Mapmentioning
confidence: 99%
“…An 11 × 11 Gaussian weighting matrix with a space constant 3.67 pixels was used to compute μ and σ as in [39]. The uncertainty reflects the degree of similarity between the corresponding pixels of a stereo pair.…”
Section: Uncertainty Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Our measure of spatial saliency strength is computed on a fused representation of the left and right frames obtained using the cyclopean image model described in [24]. 1) Luminance: Several studies have been conducted on visual attention as a function of the luminance distribution of a stereoscopic image [3]- [14].…”
Section: A Spatial Saliency Strengthmentioning
confidence: 99%